ASSESSMENT OF ENVIRONMENTAL POLLUTION WITH METALS IN SOME INDUSTRIAL REGIONS OF KOSOVO USING CHICKEN (Gallus gallus domesticus) BREAST FEATHERS - Imer Haziri; Fatgzim Latifi; Adem Rama; Muhamet Zogaj; Arben Haziri; Hamdi Aliu; Arben Sinani; Ibrahim Mehmeti; Jože Starič (Slovenian Veterinary Research, 2019)
The aim of this study was to assess the presence of metals in three regions of Kosovo using chicken (Gallus gallus domesticus) breast feathers collected from the industrial regions of Mitrovica and Obiliq and the non-industrial region of Dragash. This study was carried out from September to November 2016, and feathers were collected from 90 individual domestic chickens housed as free range. The concentrations of metals in the chicken feathers were determined with atomic absorption spectrometry (AAS). The range of average measured concentrations of metals (µg g-1) in examined regions were: Zn 109-131, Mn 6.17-31.30, Cu 22.1-27.2, Cr 5.09-19.0, Ni 12.3-15.8, Pb <0.0945-15.5, Cd 11.1-12.3 and As ><0.099-7.44. The highest average levels of metals were determined in regions (µg g-1): Dragash: Zn 131, Cu 27.2, Mn 31.3, Cr 19.0, Ni 15.8; Mitrovica As 7.44, Cd 12.3, Pb 15.5. High statistically significant differences (p><0.001) were found between the three regions for Pb, As, Mn, and Cr content. There were no significant differences (p>0.05) between the Mitrovica and Obiliq regions in terms of Zn content, Mitrovica and Dragash in terms of Cu or between the Obiliq and Dragash regions in terms of Cd content. These results should concern the environmental agencies in Kosovo and encourage them to take concrete steps by periodically checking these pollutants in these two industrial regions. Based on our results, we recommend that programmes for monitoring environmental pollution from metals could use chicken feathers as an important and valuable test material.